Data supporting A standardised Digital Twin design framework for transport system decarbonisation - Farsi, Maryam; Namoano, Bernadin; Latsou, Christina; Erkoyuncu, John Ahmet (Cranfield University, 2026)
Decarbonising transport systems is a global necessity for achieving net-zero, and Digital Twin (DT) technologies are emerging as key enablers of this transition. Despite growing interest in DT solutions, their potential support for transport decarbonisation remains in its infancy. This is mainly due to inconsistent methodological development and limited alignment with established standards. The literature shows that IoT, CPS, and embedded systems are increasingly used in DT design across the transport modes. However, they often target fragmented and function-specific use cases rather than integrated, system-level applications. This paper fills these gaps by presenting a novel Digital Twin Design Framework for transport system decarbonisation that, to the authors’ knowledge, is the first to adapt the ISO-23247 manufacturing standard to the transport domain. The study combines a systematic literature review of more than 100 studies with a Delphi consultation involving 10 experts from three UK research institutions using more than 10,000 extracted literature and workshop-derived data records.
Keywords: Digital Twin; Internet of things; Embedded systems; Intelligent transportation systems; Decarbonization